(3TQM cdjGJ GdbGfhfs - (3ehab GdOjf Hf ESMGb GdSGeQis; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s ((3eMeO Hf eMeO Hf eMeO GdeJWHH GdeYQha HLGdjfhS s)
(3ChdgG (B:s
(3bUOJ Cf CLeY dcdjGJ cJGH GdbGfhf ddTjN GdQFjS CHj Ydi Hf SjfG s
(3BNQgG (B:s
(3EPG GLJeY hQe hbQMI , aYGdL GdhQe ChdkG s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdWHs